A deep rock laboratory in the Dellen impact crater - Henkel, Herbert; Piazolo, Sandra; Wörman, Anders; Jing, Lanru (GFF, 2010)
The Deep Rock Lab is a platform to establish a comprehensive subsurface bedrock characterization approach, by integrating site characterization techniques applied from different disciplines of geo-mechanics, geochemistry, hydrogeology, structural geology, lithology and geophysics, with consideration of the effects of coupled geological processes of importance for the understanding of groundwater renewal, continental shield deformations, engineering issues related to geological disposal of nuclear waste and CO 2 , and geothermal energy retrieval in crystalline rocks. The approach will focus on the physics and chemistry of crystalline rocks and groundwater with down-the-hole measurements of relevant variables, using and developing more efficient geo-scientific site investigation techniques for deep boreholes at a chosen site, and develop more advanced down-the-hole measurements and numerical modelling methods with more advanced inversion algorithms to help integrate data interpretations and object representations. The goal is to develop this platform into a long-term research facility that can be readily used by the scientific community for both subsurface fundamental and engineering-oriented research. Such a platform will be especially important for the education of PhD students for generations to come. The integrated drilling and research facility is suggested to be located at the Dellen site. This site has an impact crater with a large range of expected physical property changes with depth, complex and multiple thermal processes that have affected the bedrock, a favorable infrastructure and local supporting activities, and a large body of existing geo-scientific data.